Maximizing Edge and Coverts for Quail and Small Game - William M. Conlin; Robert H. Giles Jr. (National Quail Symposium Proceedings, 2017)
A computer-generated table is presented, enabling the land manger to maximize on a given acreage the length of edge and the number of coverts (or corners where 3 or more cover types come together).Between-field connections are provided for sportsmen and farm machinery. The equations are presented along with diagrams of field layout and graphs of the relative changes in edge and coverts resulting from certain decisions related to management efficiency.